Espaço de vida e trabalho : o trabalho dos comissários de bordo a partir da perspectiva da atividade - Vidotti, Heloisa Giangrossi Machado (2017)
According to the Statistical Yearbook of 2015 of the air section, the number of flights and of passengers transported has been increasing year by year, considering the previous ten years. Even with this progressive increase on demand, the number of flight attendants hired by the airlines has remained almost constant. Many studies point to the negative consequences of this job on the health of the attendants, however, there is a gap on the literature regarding a thorough understanding of this profession. Thus, the goal of the present study is to further understand the discontinuities and contradictions in the work activity systems of the flight attendants. In this way, it is possible to identify the developed strategies and their impact on the health of the attendants and to suggest improvements and organizational changes to fulfill these needs. It was adopted the methodologic qualitative approach, based on the theoretical concepts of the Activity Ergonomy and Activity Theory. Flight attendants participated in the study representing the four major airlines operating in Brazil. It was employed a method and technique association for the data gathering, based on the activity analysis, where it was realized 37 semi-structured interviews with the participants, the filling of 38 surveys containing the ITRA (Inventário do Trabalho e Risco de Adoecimento) and 10 global observations of the activity of the attendants in real work situations. This theoretical-methodological choice allowed the understanding of the activity regarding the interaction between many actors and the context in which the activity is developed. As the result of the research, it was highlighted the discontinuities and contradictions on the work as well as the difficulties in the passenger customer service and relationship, as well as organizational aspects such as work scale and rest days. In this context, this study suggests as solution for the discussed problems organizational changes aiming at better work conditions. It also contributed to an increase on the understanding the work of the attendants, so far not explored on the literature, providing to the airlines and the regulatory agencies support for the prescription of changes, for an improvement in the work conditions.